นิพจน์ 34: "y" equals negative "x" plus 5.8 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+5.8−0.046<x<0.046
34
นิพจน์ 35: "y" equals "x" plus 5.9 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+5.9−0.046<x<0.046
35
นิพจน์ 36: "y" equals negative "x" plus 5.9 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+5.9−0.046<x<0.046
36
นิพจน์ 37: "y" equals "x" plus 6 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6−0.046<x<0.046
37
นิพจน์ 38: "y" equals negative "x" plus 6 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6−0.046<x<0.046
38
นิพจน์ 39: "y" equals "x" plus 6.1 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.1−0.046<x<0.046
39
นิพจน์ 40: "y" equals negative "x" plus 6.1 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.1−0.046<x<0.046
40
นิพจน์ 41: "y" equals "x" plus 6.2 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.2−0.046<x<0.046
41
นิพจน์ 42: "y" equals negative "x" plus 6.2 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.2−0.046<x<0.046
42
นิพจน์ 43: "y" equals "x" plus 6.3 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.3−0.046<x<0.046
43
นิพจน์ 44: "y" equals negative "x" plus 6.3 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.3−0.046<x<0.046
44
นิพจน์ 45: "y" equals "x" plus 6.4 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.4−0.046<x<0.046
45
นิพจน์ 46: "y" equals negative "x" plus 6.4 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.4−0.046<x<0.046
46
นิพจน์ 47: "y" equals "x" plus 6.5 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.5−0.046<x<0.046
47
นิพจน์ 48: "y" equals negative "x" plus 6.5 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.5−0.046<x<0.046
48
นิพจน์ 49: "y" equals "x" plus 6.6 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.6−0.046<x<0.046
49
นิพจน์ 50: "y" equals negative "x" plus 6.6 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.6−0.046<x<0.046
50
นิพจน์ 51: "y" equals "x" plus 6.7 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.7−0.046<x<0.046
51
นิพจน์ 52: "y" equals negative "x" plus 6.7 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.7−0.046<x<0.046
52
นิพจน์ 53: "y" equals "x" plus 6.8 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.8−0.046<x<0.046
53
นิพจน์ 54: "y" equals negative "x" plus 6.8 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.8−0.046<x<0.046
54
นิพจน์ 55: "y" equals "x" plus 6.9 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+6.9−0.046<x<0.046
55
นิพจน์ 56: "y" equals negative "x" plus 6.9 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+6.9−0.046<x<0.046
56
นิพจน์ 57: "y" equals "x" plus 7 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+7−0.046<x<0.046
57
นิพจน์ 58: "y" equals negative "x" plus 7 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+7−0.046<x<0.046
58
นิพจน์ 59: "y" equals 0.0 0 3 4 6 left brace, negative 4 less than or equal to "x" less than or equal to 4 , right bracey=0.00346−4≤x≤4
59
นิพจน์ 60: "y" equals 1.4 8 "x" to the 4th power left brace, 7.5 2 9 less than or equal to "y" less than or equal to 7.7 1 9 , right bracey=1.48x47.529≤y≤7.719
60
นิพจน์ 61: "y" equals Start Cube Root, 0.1 2 "x" , End Cube Root plus 7.3 left brace, 0 less than or equal to "x" less than or equal to 0.9 2 , right bracey=30.12x+7.30≤x≤0.92
61
นิพจน์ 62: "y" equals Start Cube Root, negative 0.1 2 "x" , End Cube Root plus 7.3 left brace, negative 0.9 2 less than or equal to "x" less than or equal to 0 , right bracey=3−0.12x+7.3−0.92≤x≤0
62
นิพจน์ 63: "y" equals "x" plus 7.1 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+7.1−0.046<x<0.046
63
นิพจน์ 64: "y" equals negative "x" plus 7.1 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+7.1−0.046<x<0.046
64
นิพจน์ 65: "y" equals "x" plus 7.2 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+7.2−0.046<x<0.046
65
นิพจน์ 66: "y" equals negative "x" plus 7.2 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+7.2−0.046<x<0.046
66
นิพจน์ 67: "y" equals "x" plus 7.3 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=x+7.3−0.046<x<0.046
67
นิพจน์ 68: "y" equals negative "x" plus 7.3 left brace, negative 0.0 4 6 less than "x" less than 0.0 4 6 , right bracey=−x+7.3−0.046<x<0.046